Evaluating of Qiraiti Books For the three lower classes of The primary stage in Iraq from an aphonrisim point of View (Journal of the College of Basic Education, 2022)
The target of this research is to evaluate Qiraiti books for the three lower classes of the primary stage from an aphonrisim point of View ,the research followed the descriptive curriculam while the research sample consists of three book which are Qiraiti book for the first class which its pages are (110) and number of its topics are (68) Qiaiti book for the second class which its pages are (120) and its topics are (43) Qiraiti book for third class its pages are (143) and its topics are(56). The researcher designed a list which consists of the religious literary and popular aphorism and their Kinds, then presented them to a group of experts for credibility according to consistancy and by using Holisty Equation by two ways: the first: analyzing the content of the targeted books, then reanalyzing then by herself a second time after (21) days , the constang coefficient was (%86), the second way: she asked the help of an expert who is qualified in analyzing the content giving him a random sample by (%50) of the analyzed material, the constant coefficient was (%84) the researcher used the percentage as a statistic means, she reachedto many results like: literary aphorisms are the most common used and themost variable. There was a lack of attention in religions and popular aphorism. In the light of the study results the researcher has many recommendations like: taking care of the balance and comprehensibility of the aphorism in general in Qiraiti books for the three lower classes of the primary stage in a way leads to an integerated knowledge for the pupils presenting suggestions for the future studies like: making a study on the intermediate stage to evaluate Arabic books according to an aphonrisim point of View.